The benefits of additive manufacturing on spare parts supply chain - Santos, Mariana Areosa (2019)
Additive Manufacturing is a technology that has been in constant development and is being adopted for more and more companies. This new method can be a solution to various problems within the company, being one the spare parts management that due to the peculiarities of their demand function becomes a high cost activity. Therefore, the objective of this thesis is finding a possible solution for reducing that cost. In order to meet such objective, the costs related to the optimal inventory management policies that should be adopted were comparedto traditional technologies and with additive manufacturing. First, a preliminary literature review has been done, with the objective of identifying referenced cost models for performing the comparative analysis. Then, a mathematical model was formulated to compare the cost of a traditional inventory policy and a policy optimized for additive manufacturing technology. The model developed has been applied to a case study from Irritec where 3 different demands were chosen to analyze the difference between having a higher or lower number of parts per year in stock. The results obtained show that the manufacturing costs are high for these parts representing a high percentage in the final cost. Although, the cost of inventory holding cost can help deciding on using one method or the other due to the large divergence between the values of inventory and this cost will influence the way the supply chain works. It is also possible to see that at lower number of pieces is more convenient to use the new technology while with the increase of pieces the traditional becomes more economical.